Something in the way she moves: biological motion, body shape, and attractiveness in women. Issue 6 (3rd July 2018) - Morrison, Edward R.; Bain, Hannah; Pattison, Louise; Whyte-Smith, Hannah
ABSTRACT: Most previous research into the attractiveness of women's bodies has relied on static stimuli such as line-drawings or photographs, particularly focusing on the role of body-mass index (BMI) and waist-to-hip ratio (WHR). However, real attractiveness judgments are invariably made on moving bodies, and movement may contain important information about attractiveness. We measured the importance of movement in attractiveness judgments by using motion-capture to isolate dynamic cues from 37 female walkers, and compare ratings of 75 participants made on these, static photographs, and the original videos. Multiple regression analysis revealed that both dynamic and static cues were important in the attractiveness of women's bodies. Furthermore, BMI and WHR predicted attractiveness, but BMI was more important in dynamic rather than static cues, while WHR was important for both static and dynamic cues. These findings suggest that movement plays a crucial part in the attractiveness of female bodies and cannot be ignored in studies of human mate choice. Furthermore, dynamic and static cues may contain differential information related to female body shape, which further research should attempt to elucidate.